PRÁTICAS DE EDUCAÇÃO AMBIENTAL EM AULAS DE QUÍMICA EM UMA VISÃO SOCIOAMBIENTAL: PERSPECTIVAS E DESAFIOS - Wildson L. P. Santos; Patrícia F. L. Machado; Roseli T. Matsunaga; Elton L. Silva; Erlete S. Vasconcellos; Valéria R. Santana (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2010)
In this paper, we draw on findings from four case studies upon environmental educational in the socio-environmental view in Chemistry lessons. From the findings, reflections about the education actions developed are showed, pointing out possible ways to approach environmental education in Chemistry lessons. Multiple data sources were used, which included interviews, surveys, students' essays, pre and post-tests and classroom observations. The case studies were carried out by post-graduates who should propose practical actions to teachers in their Master's degree dissertation. The data showed that environmental education is a challenge that requires different teaching strategies and coordinated actions in order to develop within a socioenvironmental view; which depends on the conditions of school to engage teachers in their projects.